EXPLORING VOCATIONAL HIGH SCHOOL STUDENTS’ PROBLEM IN SPEAKING SKILL - Ria Fitriana (STKIP PGRI Tulungagung, 2023)
This study was qualitative research and the participants were the tenth grade students of AP-1 at SMKN 01 Rejotangan. The objective of this study was to analyzed students’ speaking problem and the factor that affects the problem, especially for vocational students. This research used questionnaire, observation, and interview as the instruments. The result of those instruments showed that the common problem that faced by the students in speaking skill come from language aspect with mean percentage 82% from vocabulary mastery that caused the students do not have idea to speak in English. While the factors that affect the problem are nervousness and pronunciation.